Development of Multimedia Wordwall-Free Intractive Learning Media in Geography Subjects - Alraniri, Dawet; Suasti, Yurni; Ernawati, Ernawati (International Journal of Educational Dynamics, 2024)
This research is the development of learning media for geography based on multimedia word wall (website) which aims to develop learning media for geography which is monotonous to be interesting and so far it has only relied on textbooks which can make students bored every time they study in class. The development model used is the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The subject of this study was Senior High School (SHS) 1 Padangbolak Julu. The research population was students from SHS 1 Padangbolak Julu, the results of the validation test were the results of the assessment of the two validators. 3.68% "valid" with the validity category is in the interval (2.5 ?